1987
DOI: 10.1002/hlca.19870700226
|View full text |Cite
|
Sign up to set email alerts
|

Optisch aktive Alkohole aus 1,3‐Dioxan‐4‐onen: eine praktikable Variante der enantioselektiven Synthese unter nucleophiler Substitution an Acetal‐Zentren

Abstract: Secondary alcohols in enantiomcric excesses above 90% are accessible from 2-substituted 6-methyl-I ,3-dioxan-4-ones lSchmie 4 ) . The dioxanones are prepared from aldehydes and readily available (R)or (S)-3-hydroxybutanoic acid. Treatment of the dioxanones with ailyl nucleophiles or triisopropoxy(inethyl)titanium in the presence of [CI,TiX] yields the corresponding 3-alkoxy acids in diastcreoselectivities 2 95%. The 'chiral auxiliary' is removed from the alkoxy acids by treatnieiit with LiN(i-Pr), to give the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(31 citation statements)
references
References 58 publications
(40 reference statements)
0
29
0
1
Order By: Relevance
“…Tests with a mixture of 1 and degradation products thereof showed that the hydroxy acids formed are stabilized in the mixture [7] and rearrange at room temperature only after weeks to the corresponding 8-lactones, and that the hydroxy acids of the mixture in MeOH/Et,O give the corresponding methyl esters in nearly quantitative yield on addition of diazomethane in Et,O. To elucidate the configuration of the degradation products, the relative HPLC retention time(s) (tR) of the isolated diazomethane-quenched metabolite(s) of 1 were compared with that of the independently synthesized stable methyl 8-hydroxycarboxylates 2b and 3b. Products with inverted configuration at C(a) or C (8) were not anticipated because under harsher conditions than those used for the workup of the incubation with HCEL (CL Exper. Part), we never observed compounds arising from epimerization at one or both these centers [7].…”
Section: Introduction -Tetrahydrolipstatin (Thl = ( S ) -1 -{ [(2s3mentioning
confidence: 99%
See 1 more Smart Citation
“…Tests with a mixture of 1 and degradation products thereof showed that the hydroxy acids formed are stabilized in the mixture [7] and rearrange at room temperature only after weeks to the corresponding 8-lactones, and that the hydroxy acids of the mixture in MeOH/Et,O give the corresponding methyl esters in nearly quantitative yield on addition of diazomethane in Et,O. To elucidate the configuration of the degradation products, the relative HPLC retention time(s) (tR) of the isolated diazomethane-quenched metabolite(s) of 1 were compared with that of the independently synthesized stable methyl 8-hydroxycarboxylates 2b and 3b. Products with inverted configuration at C(a) or C (8) were not anticipated because under harsher conditions than those used for the workup of the incubation with HCEL (CL Exper. Part), we never observed compounds arising from epimerization at one or both these centers [7].…”
Section: Introduction -Tetrahydrolipstatin (Thl = ( S ) -1 -{ [(2s3mentioning
confidence: 99%
“…Both isomers 2b and 4 proved to be stable below room temperature for months; in solution (MeCN/H,O 6 :4,MeOH,or MeCN) at room temperature, the isomers were fairly stable, and equilibrium by 1,3-shift of the amino-acid side chain was not attained within a month. For the synthesis of the 3-epimer 3b, we initially followed the protocol developed by Seebach and coworkers for the epimerization of ethyl 3-hydroxybutyrate [8]. Tosylation of the regioisomer mixture 2b/4 provided N-(formylamino)-tosylates 5a/6a as the main products together with isocyano-tosylates 7, by-products which were formed by dehydration of the desired tosylates 5a/6a (Scheme 2).…”
Section: Introduction -Tetrahydrolipstatin (Thl = ( S ) -1 -{ [(2s3mentioning
confidence: 99%
“…Silylation of (+)- 11 , followed by condensation with (+)- 12 , promoted by TMSOTf, 62 furnished dioxanone (+)- 71 ; Petasis-Tebbe olefination 63 then provided enol ether (+)- 72 in 79% yield over the three steps without purification (Scheme 21). Exposure of (+)- 72 to our optimized Lewis acid (Me 2 AlCl) protocol, to trigger the Petasis-Ferrier rearrangement, pleasingly furnished tetrahydropyranone (+)- 73 in 70% yield as a single diastereomer.…”
Section: Resultsmentioning
confidence: 99%
“…For the synthesis of the anti isomers of 3, we started with the enantiomers of ethyl 3-hydroxybutanoate, which were converted to 10 and ent-10 using Seebachs procedure [7] followed by enolate methylation to 11, which was isolated in an anti/ syn diastereoselectivity of 95:5. The syn product could be removed by recrystallization from pentane, which is more effective than the column chromatographic procedure described in the literature.…”
Section: Resultsmentioning
confidence: 99%